ARAB RHETORIC IN THE LIFE OF PRAGMATICS HAZEEM EL QARTAJANI AS A SAMPLE - Begah, Samai (Milev Journal of Research and Studies, 2018)
This study is a modest attempt which aims at contributing to understanding and analysing the high Arab literary patrimony, through introducing one of the most eminent Arabic books, precisely: “ MINHAJE EL BOULAGA WA SIRAJE EL UDABA.” This exceptional book, in the matter of topic and methodology, was and steel is the concern of countless researchers and writers, thanks to its rich scientific, critical rhetorical and philosophical content, whose importance is not inferior to that of modern theories of pragmatics and other branches on linguistics. The content of HAZEM’s book embodies the rhetorical and the critical awareness of the ARAB patrimony and thus, the latter requires a serious study in order to unveil and exploit the mysterious treasure hid in the ancient literature. In our attempt to study ARAB rhetoric, we shall specifically shed the light on HAZEM’s one, aiming to read and analyse it pragmatically, and to study it according to, and compared with modern theory .